2001
DOI: 10.1007/s10434-001-0484-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Induction Chemotherapy and Surgical Resection for High-Grade Soft Tissue Sarcoma. Is Radiation Necessary?

Abstract: Background: Induction chemotherapy can produce dramatic necrosis in sarcomas-raising the question of whether or not radiation is necessary. This study reviews the clinical outcome of a subset of patients with high-grade extremity soft tissue sarcomas (STS) who were treated with induction chemotherapy and surgical resection but without radiation.Methods: Nonmetastatic, large, high-grade STS of the pelvis and extremities were treated with intra-arterial cisplatin, adriamycin, and, after 1995, ifosfamide. After i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…The features favouring morphological responders included fibrosis, necrosis, cholesterol clefts, haemosiderin‐laden macrophages, foamy histiocytes, inflammation, cytoplasmic degeneration, pleomorphism, bizarre nuclei, and tumour architecture . Similarly, in soft tissue and bone sarcomas, the NAC effect was assessed by evaluating the percentage of the area of tumour response relative to that of the residual tumour; patients who showed good response showed better survival . Although necrosis was long regarded as the only morphological evidence of tumour response, foamy or haemosiderin‐laden macrophages, fibrosis and smudgy chromatin were recently added as features indicative of response that should be incorporated in the evaluation of the NAC effect in soft tissue and bone sarcomas .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The features favouring morphological responders included fibrosis, necrosis, cholesterol clefts, haemosiderin‐laden macrophages, foamy histiocytes, inflammation, cytoplasmic degeneration, pleomorphism, bizarre nuclei, and tumour architecture . Similarly, in soft tissue and bone sarcomas, the NAC effect was assessed by evaluating the percentage of the area of tumour response relative to that of the residual tumour; patients who showed good response showed better survival . Although necrosis was long regarded as the only morphological evidence of tumour response, foamy or haemosiderin‐laden macrophages, fibrosis and smudgy chromatin were recently added as features indicative of response that should be incorporated in the evaluation of the NAC effect in soft tissue and bone sarcomas .…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach in assessing response to NAC has been previously used in rectal and oesophageal cancers, in which TRG has been shown to be of prognostic value; this approach has also been tested in breast and ovarian carcinomas, but with variable success . It is of note that different morphological predictors of outcome post‐NAC have been reported, such as the percentage of necrosis in high‐grade sarcomas and the size of residual tumour in ovarian serous adenocarcinoma . In the sole previous study evaluating the histological changes in RCs post‐NAC, a significant overlap was found between the NAC effect and the transurethral resection (TUR) effect.…”
Section: Introductionmentioning
confidence: 97%
“…Adjuvant radiation therapy also was administered preferentially to patients with larger, deeper tumors and with close wide or wide-contaminated margins or microscopically positive margins (72% of patients with final margins less than 1 cm; 81% of patients with final margins less than 0.5 cm). Radiotherapy generally was not administered to patients undergoing amputation, wide excisions with adequate margins associated with either an excellent response (greater than 95% necrosis) to neoadjuvant chemotherapy [19] or small (4 cm or less), subcutaneous tumors [38,39,44], or select patients presenting with widespread metastatic disease in whom chemotherapy was the only practicable chance of extending survival and local recurrence was considered unlikely in the patient's anticipated remaining life span.…”
Section: Methodsmentioning
confidence: 99%
“…Henshaw et al [6] have considered an alternative approach: omission of RT entirely in high-grade STS. Their proposal supports the use of intensive induction chemotherapy comprised of intra-arterial cisplatin and intravenous continuous-infusion doxorubicin (and ifosfamide in more recently accrued patients) as the sole adjuvant treatment in surgically managed patients.…”
Section: Omission Of Radiotherapy: Systemic Treatment In High-risk Pamentioning
confidence: 99%